Highly dispersible bis-imidazolium/WO42− modified magnetic nanoparticles: a heterogeneous phase transfer catalyst for green and selective oxidations. (9th November 2016) - Zohreh, Nasrin; Tavakolizadeh, Maryam; Hosseini, Seyed Hassan; Jahani, Mahboobeh; Pourjavadi, Ali; Bennett, Craig
Abstract : A novel magnetically recoverable catalyst was prepared in which magnetic nanoparticles were functionalized by bis-imidazolium tungstate ionic liquid molecules. Abstract : A novel magnetically recoverable catalyst was prepared in which magnetic nanoparticles (MNPs) were functionalized by bis-imidazolium tungstate ionic liquid molecules. The resulting catalyst was highly dispersible in water and selectively oxidized a wide range of alcohols and sulfides using H2 O2 as a green oxidant. The catalyst was easily recovered and reused at least 5 times under the described reaction conditions without any significant loss of reactivity.